Pengaruh Efektifitas dan Kualitas Layanan Sistem Informasi Akademik Berbasis Web terhadap Tingkat Kepuasan Mahasiswa Pada STMIK Pranata Indonesia Bekasi - Suryono Suryono (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The use of information technology has become a non-negotiable necessity, as the availability of integrated information is increasingly crucial in supporting efforts to create efficient and competitive company/organizational systems. Good academic information system management is essential for providing services to those in need and resulting in improved performance in education delivery. Accuracy and precision in presenting information are important factors in managing information. From the results of the t-test calculation calculated using SPSS 20 partially, it was found that the t-value for the effectiveness variable was 3.819 and the convenience variable was 1.745 and the quality variable was 1.933 when compared with the t-table of 1.663, it was concluded that Ho was rejected and H1 was accepted, thus partially the independent variable influenced the dependent variable, namely student satisfaction. From the results of the F-test calculation, it was found that the F-count was 9.628> from the F-table, which was 2.48, and the significance level was 0.00, which was smaller than 0.05, and this meant that overall the independent variables had an effect on the dependent variable. From the results of the R test, it was found that the determinant coefficient was 0.599 and R2 was 0.359, this meant that the influence of the independent variables on the dependent variable was 35.9% and the remaining 64.1% was influenced by other variables that had not been studied.